2015
DOI: 10.1042/cs20140329
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1–7) prevents systemic hypertension, attenuates oxidative stress and tubulointerstitial fibrosis, and normalizes renal angiotensin-converting enzyme 2 and Mas receptor expression in diabetic mice

Abstract: We investigated the relationship between Ang-(1-7) [angiotensin-(1-7)] action, sHTN (systolic hypertension), oxidative stress, kidney injury, ACE2 (angiotensin-converting enzyme-2) and MasR [Ang-(1-7) receptor] expression in Type 1 diabetic Akita mice. Ang-(1-7) was administered daily [500 μg/kg of BW (body weight) per day, subcutaneously] to male Akita mice from 14 weeks of age with or without co-administration of an antagonist of the MasR, A779 (10 mg/kg of BW per day). The animals were killed at 20 weeks of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 47 publications
1
70
0
Order By: Relevance
“…24,25 Additionally, many studies have reported oxidative stress and inflammation in the kidneys of Akita Ins2+/C96Y C57BL/6 mice, which play an important role in the pathogenesis of diabetic nephropathy. [26][27][28][29][30] However, the genetic background of Akita mutation mice contributes to the severity of albuminuria and histological changes. Gurley et al 31 studied the effect of breeding the Ins2+/C96Y mutation into the DBA/2 and 129/SvEv strains on susceptibility to diabetic nephropathy.…”
Section: Genetic Models Of Type 1 Diabetes In Micementioning
confidence: 99%
“…24,25 Additionally, many studies have reported oxidative stress and inflammation in the kidneys of Akita Ins2+/C96Y C57BL/6 mice, which play an important role in the pathogenesis of diabetic nephropathy. [26][27][28][29][30] However, the genetic background of Akita mutation mice contributes to the severity of albuminuria and histological changes. Gurley et al 31 studied the effect of breeding the Ins2+/C96Y mutation into the DBA/2 and 129/SvEv strains on susceptibility to diabetic nephropathy.…”
Section: Genetic Models Of Type 1 Diabetes In Micementioning
confidence: 99%
“…NADPH oxidase is a membrane-bound enzyme complex, which triggers ROS production through generation of superoxide radicals. Our lab found that administration of Ang 1-7 limits the activation of NADPH oxidase by attenuating the mRNA and protein expressions of NOX4, a crucial component of the NADPH oxidase complex in diabetic RPTs (7). Furthermore, Ang 1-7 also normalises the expression of antioxidant enzymes catalase and HO-1, and oxidative stress inducible proteins Nrf2 and HO-1 in diabetic RPTs (7,15).…”
Section: Ang 1-7 Limits Ros Generation and Normalises Antioxidant Patmentioning
confidence: 98%
“…Ang 1-7 binds to MasR to trigger eNOS and Akt phosphorylation (21), and stimulate the release of NO and prostaglandins. Our group previously reported that overexpression of catalase or administration of Ang1-7 normalises oxidative stress and sHTN in Akita diabetic mice (a mouse model of type 1 diabetes) and that the effect of Ang 1-7 can be reversed after treatment with MasR antagonist A-779, indicating the anti-hypertensive effect of Ang 1-7 is mediated, at least in part, via suppression of oxidative stress in diabetes (7,22).…”
Section: Ang 1-7 Reduces Systemic Hypertension (Shtn)mentioning
confidence: 99%
See 2 more Smart Citations